INTEGRATION OF ELEMENTS OF INTERIOR STYLE DECONSTRUCTIVISM IN THE INTERWAR PERIOD BUILDING’S ARCHITECTURE - Uzulena, Kristine; Apele, Diana (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2016)
The design of the building takes into account the trend of the architectural style of the time, the interior is also aged according to the main lines of a specific architectural style. Today we often face the situation when the designer wants to design the interior, appropriate to his/her time, and the architecture of the building meets another time period, another century. In such cases the most successful solution would be to find commonalities of architectural style and interior or to play on contrasts that ultimately would create a harmonious and attractive environment. The 21st century is commanded by computer system design; however, some of the buildings look like spaceships. And due to the fact that at the stage of development computer software, algorithms, and capabilities of the laser beams are used, they allow to organize and manipulate the shape of the building, different parts and create thus masterpieces of architectural art.Keeping up with the latest trends there are new styles and one of the most daring styles of the present is deconstruction. In this style the abstraction becomes extreme and works primarily according to the method of exaggeration of known motifs. Iraq-born British architect Zaha Hadid says the deconstruction is the true beginning of modern architecture, where a fascination with the scenery and feel the pride of is architects (Gimpels, 2011). It is relevant to combine too bold, contemporary style interior, for example, deconstruction, integrating it into the architecture of the building of the last century, in fact splicing „together two different worlds”. The aim of this article is to study the relevant in the 21st century interior style – deconstruction and to describe architectural style of the building designed in the interwar period in Riga, at Miera Street 82, as well as to recognize opportunities, how to integrate elements of deconstruction in this building. The authors used research methods based on the study of scientific literature and journalism, which reveal evidence of the appropriate century architecture. In the historical consideration of architectural styles content analysis is applied.